Implementation Of Drug Rehabilitation For Narcotics Addict Inmates In The Correctional System (Case Study At Tebing Tinggi Class IIb Prison) - Asina Nova Maria; Martono Anggusti; Ojak Nainggolan (PALAR | PAKUAN LAW REVIEW, 2026)
Narcotics abuse is a serious problem that affects individual health and disrupts public order and social stability. Although narcotics have benefits in health services, scientific development, and research, their abuse causes dependence and therefore requires treatment through medical rehabilitation and social rehabilitation. Law Number 35 of 2009 concerning Narcotics stipulates that addicts and victims of narcotics abuse are required to undergo rehabilitation. In the correctional context, rehabilitation is an important part of the guidance process for inmates involved in narcotics cases so that they can recover and reintegrate into society. This study aims to analyze the implementation of rehabilitation for narcotics-abusing inmates at Class IIB Tebing Tinggi Correctional Institution, identify the obstacles encountered in its implementation, and formulate efforts to optimize its implementation. This research uses an empirical legal research method with a descriptive qualitative approach through literature study and field research. The results show that rehabilitation is carried out through cooperation between the correctional institution and the National Narcotics Agency in the form of anti-narcotics counseling, skills training, medical rehabilitation, social rehabilitation, and increased supervision. However, the implementation of rehabilitation still faces various obstacles, such as limited medical personnel, inadequate facilities, and overcrowded prison conditions. Therefore, coordination between institutions, improved human resource capacity, rehabilitation infrastructure development, and sustainable policy support are needed to optimize the recovery of inmates who abuse narcotics.   Keywords: narcotics rehabilitation, inmates, correctional institution, narcotics abuse, correctional system.